Vertical Integration in High-Transaction Cost Sectors: The Case of the Bulgarian Pharmaceutical Industry - Tamara Todorova (Journal of Advanced Research in Management, 2010)
Economic theory provides various explanations for vertical integration but transaction costs seem to be a major determinant of backward, forward and lateral integration. The paper studies integration trends in the newly emerging Bulgarian pharmaceutical sector, seeking transaction cost explanations to the forward integration taking place in it. We hypothesize that asset specificity, above all, determines many of the organizational transformations and adaptations Bulgarian pharmaceutical companies are undergoing. Having special attributes, their products and assets seem to favor a larger size of the companies. Furthermore, as a low-trust, high-transaction cost economy, the Bulgarian economy dictates that a larger scale of operations be internalised within firms rather than carried out by the market.
Keywords: L42; I11; D86; D23; 330; vertical integration; transaction costs; asset specificity; distribution